Choroidal Manifestation of Smoldering Myeloma: Case Report - Sokolenko, Ekaterina; Johansson, Patricia; Ting, Saskia; Bechrakis, Nikolaos E.; Fiorentzis, Miltiadis (Klinische Monatsblätter für Augenheilkunde, 2022)
This case illustrates clinical, histopathological, immunohistochemical, and molecular pathological diagnostic testing of smoldering myeloma with atypical ophthalmic manifestations. In our case, the choroidal lesion presented as a solitary manifestation of a systemic disease. Choroidal lesions of monoclonal plasma cells are extremely rare and should be included in the differential diagnosis of amelanotic choroidal lesions, even if the histopathological examination of the primary lesion is not informative. Clinical course, immunohistochemistry, and molecular pathology are essential components of the diagnostic pathway.
Keywords: ocular oncology; smoldering myeloma; ophthalmic manifestations of multiple myeloma